Nonessential amino acids in tropical ruminant feed: Investigating grass and legume forages of Indonesia - Tresia, Gresy Eva; Anggraeny, Yenny Nur; Winarsih, Wiwik Heny; Setiasih, Setiasih; Rohaeni, Eni Siti; Mariyono, Mariyono; Pamungkas, Dicky (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to examine the concentration of nonessential amino acids (NEAAs) in ruminant feed in tropical areas, with a focus on forage grasses and legumes in Indonesia. Materials and Methods: A total of 11 grasses (Chrysopogon zizanioides, Brachiaria brizantha, Brachiaria humidicola, Paspalum dilatatum, Paspalum atatum, Chloris gayana, Pennisetum polystachion, Panicum maximum, Cenchrus biflorus, Andropogon canaliculatus, and Digotaria decumbens) and six legumes (Arachis hypogaea, Pueararia Javanica, Centrosema pubescens, Clitoria ternatea, and Arachis pintoi) were analyzed for NEAA content using high-performance liquid chromatography (HPLC). Results: Based on the results of this research, it was found that almost all NEAA content in forage was less than 3% (Serine (Ser), Alanine (Ala), Glycine (Gly), Tyrosine (Tyr), Proline (Pro), Cysteine (Cys), and Asparagine (Asn), except for glutamic (Glu) acid and arginine (Arg) in some legumes. The Glu content in grass ranges from 0.76% to 2.61%, and the Arg content ranges from 0.92% to 2.09%. These two NEAAs were most abundant in grasses and legumes, with concentrations of 5.10% to 6.27% and 3.10% to 5.53%, respectively. Conclusion: Our study concluded that Glu and Arg were the most abundant NEAAs in tropical forages in Indonesia, with legumes having a higher concentration of NEAAs compared to grasses. Among the legumes, A. hypogaea had the highest NEAA content (23.40%), while among the forages, C. zizanioides had the highest NEAA content (12.37%). However, it was observed that neither legumes nor grasses could fulfill the metabolizable TNEAAs requirements for gaining cattle (250 kg of empty body weight gain), unlike commercial concentrates, which were found to meet the requirements, especially for Arg, Glu, and thyronine. The provision of concentrate is necessary to supplement forage to meet the NEAA needs for cattle. J. Adv. Vet. Anim. Res., 10(4): 820–829, December 2023 http://doi.org/10.5455/javar.2023.j739